Politics of change - Singh, N.K. (New Delhi, 2007)
The Politics of Change draws on N.K. Singh's experience to give the reader a window into India's politics and economy, providing incisive insights into the realities of coalition politics and international fault lines. The analyses help understand why some initiatives have succeeded in transforming the economic landscape while other bills, schemes and initiatives which were launched with good intentions have either foundered because of the party in opposition or eventually emerged with scars after years of tussle. The book also highlights the challenges that India must face as its institutions evolve to keep pace with the task of governing and supporting the rapidly changing economic and social landscape.
Keywords: Economic policy